Predicting Attrition and Engagement in the Treatment of Young Offenders - Carl, Lena (International journal of offender therapy and comparative criminology, 2020)
Premature treatment termination in offender treatment is linked to negative consequences for clients, practitioners, and the criminal justice system. Therefore, identifying predictors of treatment attrition is a crucial issue in offender rehabilitation. Most studies on this topic focus on adult offenders; less is known about adolescent offenders. In our study, therapy attrition and engagement were predicted via logistic and linear regression to examine the link between pretreatment variables, engagement, and treatment failure in 161 young offenders treated in a social-therapeutic unit in Germany. Engagement could be predicted by motivation, disruptive childhood behavior, low aggressiveness, and higher age. In turn, low motivation, substance abuse, and young age predicted attrition, but their impact diminished when engagement was added to the model with only substance abuse remaining significant. The effect of substance abuse on attrition disappeared, when the offender's initial motivation was high. Implications for assessment and treatment planning are discussed.